Living death - Masterton, Graham (Masterton, Graham. Katie Maguire series., 2016)
DS Katie Maguire is at a loss. Last year, she and her team destroyed the biggest drug trafficker in Cork. So how is the city's drug trade at an all time high? Katie can't focus on this until she's solved a more pressing case: a spate of violent attacks in Cork which leave victims severely disabled and reliant on medical care abroad. But as she investigates, she realizes that the two cases might be connected. Someone is using brain-damaged victims to smuggle drugs into the country. And the only way to find out more is to go in under cover.